Quality of life and sleep in individuals with irritable bowel syndrome according to different diagnostic criteria and inflammatory bowel diseases: A comparison using data from a population-based survey - Schwille-Kiuntke, Juliane; Ittermann, Till; Schmidt, Carsten Oliver; Grabe, Hans Jörgen; Lerch, Markus M.; Völzke, Henry; Rieger, Monika A.; Enck, Paul; Schauer, Birgit (Zeitschrift für Gastroenterologie, 2022)
Background A proportion of irritable bowel syndrome (IBS) affected patients does not fulfil Rome criteria despite considerable impairment similarly to that in patients with organic gastrointestinal diseases.This investigation aims to examine differences regarding Mental (MQoL), Physical Quality of Life (PQoL), and sleep between IBS according to Rome III (IBS Rome), clinically defined IBS, inflammatory bowel diseases (IBD), and non-IBS/non-IBD individuals.Methods Data from SHIP-Trend (Study of Health in Pomerania, 2008–2012), a population-based cohort study in Germany, were used.Results Response was 50.1% (N = 4420). Prevalence was 3.5% for IBS Rome (95% confidence interval (CI): 3.0 – 4.1%, n = 148), 0.6% for clinically defined IBS (CI: 0.4 – 0.9%, n = 27), and 0.8% for IBD (CI: 0.6 – 1.1%, n = 34). Individuals with IBS Rome (4.54 (CI: –5.92; –3.17)) and clinically defined IBS (4.69 (CI: –7.82; –1.56)) had lower scores for MQoL compared to the non-IBS/non-IBD group. PQoL scores were lowered in IBS Rome (6.39 (CI: –7.89; –4.88)) and IBD (5.37 (CI: –8.51; –2.22)), but not in clinically defined IBS compared to the non-IBS/non-IBD group. IBS Rome was the only gastroenterological condition with higher odds of sleeping problems (odds ratio (OR) “falling asleep”: 1.74; CI: 1.29; 2.36; OR “remaining asleep”: 1.73; CI: 1.26; 2.38).Conclusions IBS Rome is associated with reduced MQoL, PQoL, and sleep problems. Clinically defined IBS is associated only with reduced MQoL. Heterogeneity within IBS affected patients should be considered in clinical routine and screening for daily life impairment should be performed.
Keywords: Lebensqualität; Schlaf; Reizdarmsyndrom; Epidemiologie